Efisiensi Saluran Drainase Eksisting pada Sistem Drainase Daerah Aliran Sungai Selumit Kota Tarakan Kalimantan Utara - Hadun , Moses; Khaerudin , Dian Noorvy ; Khaerudin , Dian Noorvy ; Sulistyani , Kiki Frida (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
In the City of Tarakan, there is a network of drainage systems that have different dimensions and water debit sizes. In the Selumit River Basin drainage system, runoff often runs on the road when it rains. This is caused by existing runoff. Yet according to planning calculations and based on dimensional calculation results, the channel can still accommodate existing runoff discharge. This is caused by some inefficient channels. Inefficient channels can cause runoff. Based on efficiency calculations, the Selumit River Basin drainage system in Tarakan City is an efficient channel, with an average percentage of efficiency of 97%. This means that only 3% of the percentage of water that escapes from the difference in water entering the channel with water coming out of the drainage channel. According to the Efficiency calculation, there are several very efficient drainage channels, namely channels with scheme numbers 3, 4, 6, 7, 10, 13 and 14 with each value of efficiency percentage is 100%. And there are some inefficient channels among which are channels with the number scheme 1, 2, 5, 8, 9, 11, 12, 15, 16, 17, 18, 19, and 20, with each percentage value of efficiency is 93% , 84%, 99%, 99%, 98%, 99%, 99%, 95%, 98%, 97%, 97%, 99%, and 92%. The channel with the lowest percentage of efficiency is 84% found in the channel with scheme number 2. It means that the runoff water in the drainage channel is as complicated as between 2% -16%. Based on the analysis, an alternative solution to the problem of an inefficient drainage system was formulated is to streamline an inefficient drainage channel.